Selenium‐Chitosan Reduces Postharvest Decay of Red Globe Grapes by Improving Disease Resistance During Cold Storage - Yaping Liu; Wei Wang; Yanan Cao; Li Li; Zhixuan Fan; Jianbing Di; Yu Wang; Lixin Zhang (eFood)
ABSTRACT The preservation of grapes during storage and transportation has long been a challenge due to the presence of Botrytis cinerea. Studies have shown that chitosan and selenium are effective in preserving fruits and vegetables during storage. This study investigated the effect of selenium‐chitosan (25 mg L−1 selenium and 1.0% chitosan) treatment on Red Globe grapes' disease resistance during storage at 0°C. The results indicated that treatment with selenium‐chitosan significantly reduced the decay rate of grapes from 41.79% to 4.93% at 60 days of storage. Additionally, the treatment increased the activities of POD and CAT and decreased the activity of PPO. The application of selenium‐chitosan resulted in increased activity of PAL, C4H, and 4CL which was related to the phenylalanine pathway, leading to the accumulation of phenolic compounds and improved disease resistance in grapes. RT‐qPCR analysis revealed that the upregulation of VvPAL, VvC4H, and Vv4CL was delayed in grapes treated with selenium‐chitosan. Their expression levels were significantly lower than those of the control grapes, with reductions to 2.37%, 2.02% and 10.60 at 60 days of storage, respectively. After inoculation with Botrytis cinerea, grapes treated with selenium‐chitosan effectively limited the growth of Botrytis cinerea mycelium. These results suggest that selenium‐chitosan treatment significantly improves resistance to microbial infestation and limits fungal growth after exposure.